Change Management Process as a Skill for Global Talent in Integration of Companies - Lubis, Fatimah Malini; Simatupang, Teddy Juanda (Proceeding Kilisuci International Conference on Economic & Business, 2023)
Research aim : The purpose of this study is to identify resistance to change and recommend one or more methods to manage that resistance. Design/Method/Approach : The research was conducted qualitatively on an industrial and capital-intensive strategy that underwent a change in strategy or transformation as part of the company's integration process. Research Finding : Despite good planning, reactions that arise during the process and after the integration deadline requires separate treatments. Handling this requires formal and informal networks where the human role is more important than strategy, emotions have a greater impact than logic, and behavior is more persuasive than words. Theoretical contribution/Originality : Practitionel/Policy implication : Research limitation : Keywords : Talent, Pandemic, Disruption